SÄ«rah Of The Prophetâ€™s Early Life In Musnad of Aá¸¥mad: An Analytical Study Of QurÊ¿Änic References In SÄ«rah Nabawiyyah (Sains Humanika, 2017)
Reviews of early Muslim sources confirm that some verses of the Qurâ€™Än have been perceived by Muslim scholars as direct references to the narratives of the Prophetâ€™s early life. These selected verses are deemed to contain information about Muá¸¥ammadâ€™s genealogy, birth, childhood and other aspects of his youth.Â  Modern scholars have, however, argued about the appropriateness and authority of these Qurâ€™Änic references as being the true bearers of information of the Prophetâ€™s biography. Since the á¸¥adÄ«th is regarded as an authoritative exegetical tool employed to explore more deeply the meaning of the Qurâ€™Än, and one of which contains a vast source of information about the Prophetâ€™s life, it is indispensable to analyse the works of á¸¥adÄ«th and its scholarsâ€™ views on the narratives of sÄ«ra nabawiyya. This study aims to explore the narratives of the Prophetâ€™s early life in Musnad of Aá¸¥mad and analyse Aá¸¥madâ€™s perspective regarding Quranic references to the Prophetâ€™s early life. The study is qualitative in nature in which the researcher utilised both critical and analytical approached as its methodology. The study in its finding espouses that the rarity of Qurâ€™Änic reference to Muá¸¥ammadâ€™s early life in Musnad of Aá¸¥mad, an enormous inventory of á¸¥adÄ«th of the ninth century, indicates one scholarâ€™s views about Muá¸¥ammadâ€™s early life. It is obvious that Aá¸¥mad make no connection between the Quran and the narratives of the Prophetâ€™s early life, even though verses that are widely used by the author of sÄ«ra as an allusion to Muá¸¥ammadâ€™s early life.
Keywords: SÄ«ra Nabawiyya; Musnad; Aá¸¥mad; Prophet Muá¸¥ammad; narrative